Students' Perception of Using ChatGPT as an AI-Integrated Tool in the Malay Language (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
This study examines the perceptions of students using ChatGPT in the Malay language. To meet the aims, We adopted the theory of technology acceptance model (TAM). The study focuses on system quality, information quality, service quality, user satisfaction, perceived net benefits, and awareness of ethics and plagiarism. Data were collected through a Qualtrics survey. The finding informed that the system quality of ChatGPT achieved a mean score of 3.375, indicating ease of use and flexibility. Information quality received a mean score of 3.27, suggesting accuracy and usefulness. Service quality scored 3.207, reflecting adequate technical support and consistent performance. User satisfaction was remarkably high, with a mean score of 3.334, demonstrating strong confidence and contentment with ChatGPT’s functionality. Perceived net benefits scored 3.337, highlighting language skills and communication efficiency enhancements. Meanwhile, the ethical considerations were moderately addressed, with a mean score of 3.115, indicating a need for improved education on responsible use. The findings suggest that ChatGPT is a valuable tool for the Malay language, with areas for further enhancement in information quality and ethical practices. At the same time, understanding users’ perceptions will also help create between relevant AI resources, inform policies for ethical AI use, and enhance learning experience for Malay learners.